Routledge handbook of sexuality, health and rights - Aggleton, Peter; Parker, Richard Guy (Routledge, 2010)
This handbook surveys the state of the discipline, including examination and discussion of emerging, controversial and cutting edge areas. It is an essential reference for all academics and researchers in the fields of sexuality studies, sexual health and human rights, as well as very useful reading for more advanced students.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; droits; outils; ouvrages de références; périodes historiques; santé; santé reproductive; sexualité; thématiques

Dictionnaire des cultures gays et lesbiennes - Eribon, Didier; Haboury, Frédéric; Lerch, Arnaud (Larousse, 2003)
Dictionnaire illustré et international consacré aux cultures gays et lesbiennes contemporaines (depuis la fin du XIXe siècle). Plus de 570 articles(2 millions de signes en tout), dont 50 dossiers thématiques, qui couvrent tous les aspects du sujet : - références culturelles et artistiques communes (d'Absolutely Fabulous à Virginia Woolf, de Pedro Almodóvar à Andy Warhol.), - associations (Act Up.), - théoriciens (Michel Foucault.), - événements (Lesbian and Gay Pride.), - mours et modes de vie (sida, sexualités.), - aspects légaux (couple, adoption.), - gay and lesbian studies (histoire, sociologie, queer theory.), etc.
Section: 548 pages : illustrations (certaines en couleur), photogr. (certaines en couleur) ; 27 cm
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; queer; sexualité; soc2014; thématiques; études gaies et lesbiennes